Assessment of extensor hallucis brevis stiffness and microcirculation in diabetes: shear wave elastography and contrast-enhanced ultrasound - Yan, Fuqiang; Cai, Mingli; Li, Meirong; Huang, Shanshan; Guo, Jingyi; Lin, Jinmiao; Lyu, Guorong (Frontiers in Endocrinology, 2025)
BackgroundDiabetic foot complications, driven by microvascular dysfunction, remain a leading cause of morbidity and amputations. Early detection of microcirculatory and biomechanical alterations in vulnerable muscles, such as the extensor hallucis brevis (EHB), may contribute to risk stratification. However, noninvasive tools for quantifying these changes are lacking.MethodsThis cross-sectional study enrolled 90 participants stratified into healthy controls, uncomplicated type 2 diabetes (T2DM), and T2DM with microvascular complications (MC). Shear wave elastography (SWE) measured EHB stiffness (mean Young’s modulus, Emean), while contrast-enhanced ultrasound (CEUS) assessed perfusion dynamics (transcapillary transit time [ΔAT], net enhancement intensity [ΔPI]). Diagnostic accuracy and reproducibility were evaluated via ROC analysis and intra-class correlation coefficients (ICC).ResultsEmean increased progressively across groups (control: 11.88 kPa; T2DM: 15.78 kPa; T2DM+MC: 18.57 kPa; P < 0.01). T2DM+MC exhibited prolonged ΔAT (89.5 s vs. 50.5 s in controls) and reduced ΔPI (5.0 dB vs. 7.0 dB; P < 0.01). ROC analysis demonstrated high diagnostic accuracy for ΔAT (AUC = 0.970), Emean (AUC = 0.947), and ΔPI (AUC = 0.931) in detecting MC. Both SWE and CEUS showed excellent reproducibility (ICC > 0.80).ConclusionSWE and CEUS provide robust, noninvasive biomarkers for early diabetic microvascular complications. The EHB’s unique susceptibility to stiffness and perfusion deficits highlights its clinical value, which may facilitate diabetic foot risk assessment and guide timely interventions to mitigate ulceration and amputations.